Costly Information Acquisition in Decentralized Markets: Experimental Evidence - Asparouhova, Elena; Bossaerts, Peter; Yang, Wenhao (Management Science, 2024)
This study tests the rationality of the decisions to purchase information, the informational efficiency of prices, and the optimality of the resulting allocations in decentralized markets with a series of laboratory experiments. The theory predicts that markets with dispersed information and natural buyers and sellers converge to a fully revealing equilibrium. It is profitable to pay for information, and as such, the Grossman-Stiglitz paradox does not emerge. Statistically significant improvements in both price efficiency and allocative efficiency are documented across trading periods. In contrast to the theory, which predicts that the higher the number of informed agents, the stronger the individual incentives to invest in information, the and the more data present the opposite result. The price of information is higher when there are fewer informed agents. The result can be explained by boundedly rational decision making. This paper was accepted by Yan Chen, behavioral economics and decision analysis. Funding: This work was supported by the National Science Foundation [Price Quality in Dark Markets Grant 1426428]. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2023.4976 .